Epidemiologic principles and food safety - Lasky, Tamar (New York ; Oxford : Oxford University Press, 2007)
Describing the ways epidemiologic principles are applied to meet the challenges of maintaining a safe food supply, this book addresses prevention and control of foodborne illnesses. The book concludes by describing the regulatory context that shapes food safety activities at local, national and international levels.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Food -- Safety measures; Epidemiology; Food supply; Food -- Toxicology